Zone 1 trauma: wound dehiscence compared to primary trauma - Choudhry, Hassaam S.; Seery, Christopher W.; Dastjerdi, Mohammad H. (Digital Journal of Ophthalmology, 2024)
Introduction The study aims to assess if zone 1 globe injuries hold a favorable prognosis for all situations, including wound dehiscence, or just primary traumatic injuries. Methods Retrospective cross-sectional chart review of patients who underwent open-globe injury repair from January 1, 2019, to December 1, 2020, at an urban hospital setting were evaluated for final visual outcomes, associated ocular pathology, long term complications, and need for further surgeries. Results Fifty-eight eyes were identified including 38 primary trauma cases and 20 dehisced wounds (11 penetrating keratoplasties, 5 clear corneal incisions, 1 laceration, 1 extracapsular cataract extraction, 1 radial keratotomy, 1 tectonic graft). Dehisced wounds had more posterior segment pathology compared to primary trauma, including choroidal hemorrhage, vitreous hemorrhage, retinal detachment, and choroidal effusion (all 20% vs 2.63%, 5.26%, 5.26%, and 0% resp.), as well as vitreous prolapse (20% vs 2.63%) and uveal prolapse (80% vs 36.84%). Dehisced wounds had more traumatic aphakia (40% vs 0%) and dislocated lenses (15% vs 0%). Primary trauma was more likely to have traumatic cataracts (55.26% vs 10%) or no lens changes (44.74% vs 25%). 10% of dehisced wounds required enucleation (0% of primary trauma). Cataract/secondary intraocular lens surgery was performed in 34% of the primary traumas (10% in dehisced wounds). Primary traumas achieved 20/40 vision or better in 44.74% (10% in dehisced wounds). 7.89% patients with wound dehiscence ended with no light perception (none in primary trauma). Conclusions Zone 1 open-globe injuries due to wound dehiscence may exhibit worse prognosis compared to primary trauma open globe injury. More important in determining prognosis of open-globe injuries compared to the zone of injury be the source or epidemiology of trauma.